Analysis of Community Preferences in Islamic Banking - Denata, Betria; Izmuddin, Iiz; Zuwardi, Zuwardi; Alfin, Aidil (International Journal of Education, Information Technology, and Others, 2025)
Sharia banking in Nagari Malalak Timur has great potential, but the community still actively uses conventional banks, and only a few choose sharia banks as their primary option for financial transactions. This low level of interest is due to a lack of understanding of Islamic principles, limited access to Islamic bank branches, and the perception that Islamic products are more complicated and expensive than conventional banks. The purpose of this study is to identify and analyze the level of understanding of the people of Nagari Malalak Timur regarding Islamic banking products and services, as well as the reasons for choosing conventional banks. This study uses a qualitative approach, with a descriptive qualitative research type. The research location was in East Malalak Village, Malalak District, Agam Regency. Data collection techniques used observation, interviews, and documentation. Data analysis techniques used data reduction, data presentation, and verification or conclusions. The results of the study in Nagari Malalak Timur show that the community's preference for Islamic banks is still low. Influencing factors include limited knowledge, the habit of using conventional banks, and difficult location and accessibility. The community finds it difficult to understand the concept of Islamic banking and prefers conventional banks because of familiarity. To increase the use of Islamic banks, there needs to be an effort to raise awareness and open branches in the area.